Retelling social inequalities in the era of market competition: Review and discussion for sustainable welfare development - Pechdin, Watchara; Sarnkhaowkhom, Chawapon; Kanthanetr, Sudarat; Willemse, Martin Pieter (Frontiers in Sociology, 2023)
As the prevalence of social inequalities has become increasingly evident, the implementation of social welfare policies in countries across the globe has faced considerable obstacles and has not yielded the desired results. In spite of the fact that social welfare policies are formulated to reduce inequalities in society, the recent increase in inequalities has raised questions about whether or not welfare implementation is appropriate to the social context where resource distributions are dominated by economic structure. Inspired by this, the aim of this paper is to echo contemporary perspectives on social inequality and challenges that have contributed to its development under the economic system of market competition. The contemporary matters arising from social inequalities, which include intergenerational inequality, gender-based inequality, health inequality, and education inequality, are examined in accordance with the context of market competition. This would hopefully enable academicians to timely recognize and address ideological and paradoxical social inequalities and welfare development within their society.